Cucumber (Cucumis sativus L.) Growth and Yield as Respons by Dolomite and Potassium Application on Peat Soil - Padang, Agri Andi Saputra; Herawati, Reny; Barchia, M. Faiz; Widiyono, Heru; Simanihuruk, Bilman W. (TERRA : Journal of Land Restoration, 2023)
This study aimed to determine the appropriate dose of dolomite, dose of K fertilizer, and the interaction of the treatments on the growth and yield of cucumber on peat soil soil. This research was conducted in Medan Baru, Muara Bangka Hulu Sub-district, Bengkulu City at an altitude of ± 10 meters above sea levelfrom September to December 2021. The experiment method used was a factorial Randomized Complete Block Design (RCBD) consisting of two factors; first, dose of dolomite with 3 levels consisting of 0.00 tons ha-1, 1.25 tons ha-1, and 2.5 tons ha-1 Dolomite, and the second, dose of potassium fertilizer consisting of 4 levels; 0 kg ha-1, 200 kg ha-1, 400 kg ha-1, and 600 kg ha-1 with 3 replications. Each unit of the experiment pot was planted with 3 plants therefore whole samples were obtained 108 experimental plant units (polybags). Cucumber growth and yield significantly responded to the dolomite and potassium application. The interaction between the dolomite and the potassium applied significantly to the cucumber planted shown by plant length, the diameter, and length of the fruit.